2018
DOI: 10.1111/cas.13524
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle‐related and expression‐elevated protein in tumor overexpression is associated with proliferation behaviors and poor prognosis in non‐small‐cell lung cancer

Abstract: The cell cycle‐related and expression‐elevated protein in tumor (CREPT) is overexpressed in several human malignancies. However, the clinical relevance of CREPT expression and its biological role in non‐small‐cell lung cancer (NSCLC) remains unclear. In this study, we detected the expression of CREPT in both NSCLC tissues and cell lines by immunohistochemistry, Western blot analysis, and RT‐PCR. The correlation between CREPT expression and clinicopathologic features was analyzed in 271 NSCLC patients. The prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Cell migration and metastases formation are crucial for malignant progression, which leads to increased mortality in cancer patients. Recent studies revealed the oncogenic potential of CREPT expression in multiple cancer types, including correlation with poor prognosis, induction of cell proliferation in vitro, and tumorigenesis in vivo [26][27][28]. Knockdown of RPRD1B increased cell sensitivity to treatment in endometrial adenocarcinoma, which suggests a therapeutic potential for targeting CREPT [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration and metastases formation are crucial for malignant progression, which leads to increased mortality in cancer patients. Recent studies revealed the oncogenic potential of CREPT expression in multiple cancer types, including correlation with poor prognosis, induction of cell proliferation in vitro, and tumorigenesis in vivo [26][27][28]. Knockdown of RPRD1B increased cell sensitivity to treatment in endometrial adenocarcinoma, which suggests a therapeutic potential for targeting CREPT [21].…”
Section: Discussionmentioning
confidence: 99%
“…The transwell migration and invasion assays were conducted using 6.5‐mm transwell insert chambers (Corning Costar Corp.) with or without matrix gel as reported previously . After 24 hours treatment with or without 2 mmol/L melatonin, the migrated or invaded cells were fixed, stained with 0.1% crystal violet, photographed, and counted.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of CHCHD2 and HIF-1α protein in all the tissue sections of the subjects were investigated by rabbit antibodies (anti-CHCHD2, diluted 1:50, ABGENT, San-Diego, CA or anti-HIF-1α, diluted 1:100, Proteintech™, Chicago, USA). The detailed operation process and staining score of immunohistochemistry accordance with our previous methods [18]. The final immunohistochemical staining score reported is the average of the scores from the tow investigators.…”
Section: Immunohistochemistrymentioning
confidence: 99%